On the mechanism of colloidal silica action to improve flow properties of pharmaceutical excipients - Tran, Diem Trang; Majerová, Diana; Veselý, Martin; Kulaviak, Lukáš; Ruzicka, Marek C.; Zámostný, Petr (International journal of pharmaceutics, 2019)
[Display omitted] The mechanism of colloidal silica action to improve flow properties of pharmaceutical powders is known to be based on inter-particle force disruption by silica particles adhered to the particle surface. In the present article, the kinetic aspects of this action are investigated, focusing on non-spherical particles of different size. Blends comprising microcrystalline cellulose or calcium hydrogen phosphate dihydrate and colloidal silica were examined using powder rheometer. The blends were formulated to represent effects of particle size, surface texture, colloidal silica loading, and mixing time. Pre-conditioning, shear testing, compressibility, and flow energy measurements were used to monitor flow properties. Components and blends were analyzed using particle size analysis and scanning electron microscopy (SEM), using energy dispersive spectroscopy (EDS) and back-scattered electron (BSE) detection to determine surface particle arrangement. All studied parameters were found to have substantial effects on flow properties of powder blends. Those effects were explained by identifying key steps of colloidal silica action, which were found to proceed at substantially different rates, causing the flow properties change over time being dependent on the blend formulation and the component properties.